Avaliação das instituições de longa permanência para pessoas idosas - Mirna Rodrigues Costa Guimarães (2021)
The objective of this study was the development and validation of a Multidimensional Assessment Matrix (MMA) composed of indicators created using the variables of the 2018 Unified Social Assistance System Census (SUAS Census) to describe the quality of Brazilian LSIAPs, and compare the performance achieved between the regions of the country. This is a descriptive ecological study with secondary public data from the LSIAP participating in the SUAS 2018 Census. The MMA was developed based on the Integrated Multidimensional Theoretical Model of Quality and Service by Rantz et al. (1999). 66 variables from the SUAS Census were selected for the elaboration of the Matrix, which was validated by the modified Delphi technique, with the participation of 15 experts, through the online platform Survey Monkey. Eighteen indicators were proposed for the MMA and two validation cycles were needed until consensus was reached. Quality parameters, based on literature, legislation or statistical criteria were used to classify the performance of institutions for each indicator as “incipient”, “under development” or “desirable”. The percentages of LSIAP with “desirable” performance were represented by means of maps, according to the Brazilian regions. The disparity index was obtained for each indicator and expressed the average deviation in the percentage of institutions with desirable performance among Brazilian regions. More than 70% of the institutions showed desirable performance only in three indicators: "Favoring the Family Bond" (94.18%), "Adequate physical structure" (87.51%) and "Valuing the team of professionals" (76.22 %). “Incipient” performance was observed for 83.81% of the institutions regarding the indicator “Professionals for leisure activities”. Disparities were observed in the percentages of LSIE with “desirable” performance among Brazilian regions, whose indices ranged from 6.21 (favoring family ties) to 48.48 (multiprofessional team in the health area). Brazilian LSIEs have valued the team of professionals, have physical structure and favor the family bond. There is a need for advances in the proportion of caregivers of elderly people, composition of the multidisciplinary team, improved accessibility, as well as the need to expand the supply of health promotion actions, government support, suppression of exclusionary differentiation criteria and expansion of services to overcome overcrowding. Regional disparities indicate unequal performance of institutions in the national territory.